Early changes in microRNA expression in Arabidopsis plants infected with the fungal pathogen Fusarium graminearum - Savio S. Ferreira; Suman Pandey; Jesseca Hemminger; Serdar Bozdag; Mauricio S. Antunes (PLoS ONE, 2025)
Plants respond to biotic stressors by modulating various processes in an attempt to limit the attack by a pathogen or herbivore. Triggering these different defense processes requires orchestration of a network of proteins and RNA molecules that includes microRNAs (miRNAs). These short RNA molecules (20–22 nucleotides) have been shown to be important players in the early responses of plants to stresses because they can rapidly regulate the expression levels of a network of downstream genes. The ascomycete Fusarium graminearum is an important fungal pathogen that causes significant losses in cereal crops worldwide. Using the well-characterized Fusarium-Arabidopsis pathosystem, we investigated how plants change expression of their miRNAs globally during the early stages of infection by F. graminearum. We have created a catalog of miRNAs that have differential expression in infected samples even before any visual symptoms of the infection are present. In addition to miRNAs that have been previously implicated in stress responses, we have also identified evolutionarily young miRNAs whose levels change significantly in response to fungal infection. Some of these young miRNAs have homologs present in cereals, which suggest that some of these miRNAs could be drivers of stress response. By examining if the miRNAs in this catalog have causal roles in plant infection response, a unique path toward development of plants with increased resistance to fungal pathogens can be developed.